Pemahaman Ayat Poligami dengan Pendekatan Linguistik - Anan Marliansyah; Muh. Asharif Suleman; Ushie Uswatun Hasanah; Kurnia Utami Nursholichah; Riza Febriansyah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to introduce a linguistic approach in studying Islamic studies problems. Oni’s research also introduces Islamic studies on polygamy using Syahrur’s perspective linguistic approach. This research uses a qualitative approach. This research is a library study type, namely content analysis. The research steps were carried out by exploring the research theme until a deep understanding of the linguistic approach and the concept of the Shahrur linguistic approach to the polygamy verse were obtained. The research result show that the linguistic approach in the study of Islam is an effort made to study Islamic problems using a linguistic perspective. The linguistic approach provides an understanding that Islam is very open and can be stuudied using scientific approaches. The linguistic approach aims to study the texts of the Qur’an to find the original meaning of the texts being studied. The result of islamic studies using a linguistic approach provide original meaning so that it can be practiced properly and correctly as it should be. Polygamy in Syahrur’s view is remarrige to widows who have orphan children. Linguistic approach to polygamy, shahrut has different meanings from those determined by the majority of ulama. Syahrur uses linguistic analysis, mathematical analysis and semantic analysis approaches.